Philosophy in a time of lost spirit : essays on contemporary theory - Beiner, Ronald, 1953- (Toronto [Ont.] : University of Toronto Press, 1997)
In this collection of his essays and reviews, Ronald Beiner probes the boundaries of our social world and develops his own intellectual challenge to liberalism in a critical review of contemporary thinkers.
13 Hannah Arendt and Leo Strauss: The Uncommenced DialogueAppendix: Response from a Colleague, with a Rejoinder -- 14 Eros and the Bourgeoisie -- 15 Left-Wing Conservatism: The Legacy of Christopher Lasch -- 16 Hermeneutical Generosity and Social Criticism -- 17 Thin Ice -- III: Political Judgment Revisited -- 18 Practical Wisdom -- 19 Science and Wisdom -- 20 Rereading Hannah Arendt's Kant Lectures -- NOTES -- INDEX -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Liberalism; Libéralisme.; liberalism; POLITICAL SCIENCE -- Political Ideologies -- Conservatism & Liberalism; POLITICAL SCIENCE -- History & Theory; Liberalism; Liberalismus; Electronic books; e-books.; Livres numériques.